2000
DOI: 10.1001/jama.283.17.2249
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Child Passenger Deaths and Injuries Involving Drinking Drivers

Abstract: These data indicate that the majority of drinking driver-related child passenger deaths in the United States involve a child riding unrestrained in the same vehicle with a drinking driver. Typically, the drinking driver transporting the child is old enough to be the child's parent or caregiver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 13 publications
1
36
1
1
Order By: Relevance
“…Dos terceras partes de estas defunciones involucran a un niño en un vehículo conducido por un sujeto con problemas de alcoholismo, habitualmente el padre o tutor de estos. 25 Una tercera parte de defunciones en niños son causadas por menores de 21 años (edad legal en ese país para consumir bebidas alcohólicas), que conducían bajo los efectos del alcohol. 26 La prevalencia de consumo riesgoso en los jóve-nes de este estudio es elevada, pues uno de cada cinco a seis hombres menores de 25 años tienen este consumo.…”
Section: Discussionunclassified
“…Dos terceras partes de estas defunciones involucran a un niño en un vehículo conducido por un sujeto con problemas de alcoholismo, habitualmente el padre o tutor de estos. 25 Una tercera parte de defunciones en niños son causadas por menores de 21 años (edad legal en ese país para consumir bebidas alcohólicas), que conducían bajo los efectos del alcohol. 26 La prevalencia de consumo riesgoso en los jóve-nes de este estudio es elevada, pues uno de cada cinco a seis hombres menores de 25 años tienen este consumo.…”
Section: Discussionunclassified
“…First, percentages of restraint use among child passengers involved in crashes in each age group were examined using KCARS data, and RR (relative risk) ratios of the older child sub-group were calculated in comparison to younger child passenger sub-group. Second, drivers were paired with each crash-involved child in the vehicle according to the double-pair comparison method because driver characteristics could be stronger predictors of child restraint use [12]. This method has been commonly used in child passenger safety literature if the driver and at least one child occupant are in a vehicle involved in a crash.…”
Section: Methodsmentioning
confidence: 99%
“…The recommendation was made that mechanisms to increase safe-driving practices of drivers transporting child passengers could potentially decrease the number of child passenger injuries from crashes. Quinlan et al [12] examined the characteristics of crashes involving child passenger death and injuries associated with drunken drivers and identified opportunities to prevent such crashes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Its many health effects, both adverse and beneficial, have been well documented. For example, in 1998, alcoholrelated motor vehicle crashes claimed 15 935 lives in the United States, accounting for 38% of all traffic fatalities.1 Two articles 2,3 in this issue of THE JOURNAL highlight the particular circumstances of children who die in alcoholrelated motor vehicle crashes and shed some light on the relationships of these children to the alcohol-impaired drivers who caused their deaths.Quinlan and colleagues 2 from the Centers for Disease Control and Prevention examined the characteristics of children who were injured as passengers in alcohol-related motor vehicle crashes and the incidence of these crashes. Based on data from the Fatality Analysis Reporting System (FARS) for the years 1985-1996 and the General Estimates System for the years 1988-1996, the authors found that each year in the United States, alcohol-impaired driving resulted in more than 16000 injuries and claimed an average of 463 lives among child passengers aged 14 years and younger.…”
mentioning
confidence: 99%
“…In addition to passengers, Margolis et al included children younger than 16 years who, while walking or bicycling, were killed by drinking drivers. Unlike the study by Quinlan et al, 2 in which a well-established imputation method was applied to estimate the blood alcohol concentrations (BACs) for drivers without data on alcohol test results, alcohol involvement in the study by Margolis et al 3 was based solely on police assessment. Despite these differences in methods, the 2 studies found consistent and complementary results.…”
mentioning
confidence: 99%